2017
DOI: 10.24820/ark.5550190.p009.905
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of (E)-cinnamic acid, (E)-2-styrylthiazole and (E)-2-[2-(naphthalen-1-yl)vinyl]thiazole derivatives

Abstract: Cinnamyl-and thiazole-based compounds have been shown to exhibit diverse medicinal properties and a series of twelve (E)-2-styrylthiazole and (E)-2-[(naphthalen-1-yl)vinyl]thiazole derivatives, which are conjugates of both systems and which satisfy the "Lipinski rule of 5", have been synthesised and subjected to in vitro biological screening. While insignificant inhibition (60-98% viability at 10 µM) of HeLa (cervical cancer) cells was noted, all five of the (E)-2-[naphthalen-1-yl)vinyl]thiazole derivatives pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Compounds 2 – 4 were made by routes based on a recently published method for synthesizing pitolisant (Scheme ). Known cinnamic acids 5 – 7 were synthesized by Knoevenagel condensations , and reduced by standard methods to provide the corresponding known hydrocinnamyl alcohols 8 – 10 . These intermediates were converted into targets 2 – 4 by adding KO- t -Bu and spirocyclic ammonium bromide 11 , which is produced by the reaction of piperidine with 1-bromo-3-chloropropane. , The corresponding hydrochloride salts were made by standard reactions and were crystallized by methods used for pitolisant hydrochloride.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 2 – 4 were made by routes based on a recently published method for synthesizing pitolisant (Scheme ). Known cinnamic acids 5 – 7 were synthesized by Knoevenagel condensations , and reduced by standard methods to provide the corresponding known hydrocinnamyl alcohols 8 – 10 . These intermediates were converted into targets 2 – 4 by adding KO- t -Bu and spirocyclic ammonium bromide 11 , which is produced by the reaction of piperidine with 1-bromo-3-chloropropane. , The corresponding hydrochloride salts were made by standard reactions and were crystallized by methods used for pitolisant hydrochloride.…”
Section: Resultsmentioning
confidence: 99%
“…2‐Styrylthiazole‐4‐carboxylic acid was prepared according to the reported procedures. [ 18 ] 2.0 g of l ‐Histidine methyl ester dihydrochloride (8.26 mmol) was dispersed in dry dichloromethane (250 mL). To this solution, 2.09 g of triethylamine (20.66 mmol) were added.…”
Section: Methodsmentioning
confidence: 99%
“…All the chemical intermediates (3a-j) were obtained by the reaction between corresponding aldehydes (1) and malonic acid (2), via Doebner-Knoevenagel condensation ( Figure 3), with yields ranging from 45 to 94% [76,77]. Additionally, 1 H Nuclear Magnetic Resonance (NMR) spectra revealed that the intermediates (3a-j) were obtained in an (E)-configuration, confirmed by large vinylic coupling constant (J) values, ranging from 15.8 to 16.1 Hz [77,78]. Moreover, 1 H NMR analysis showed that the chemical shifts (δ) for the hydroxyl (OH) from the carboxylic acid can appear between 12.38 and 12.71 ppm.…”
Section: Chemistrymentioning
confidence: 99%
“…These procedures are adaptations from works previously reported [107][108][109]. In general, an adaptation of methods described by Luo and collaborators (2015) was used [110], through a Knoevenagel condensation Doebner modification reaction [77]. In a bottom flask (50 mL) containing 6 mL pyridine, the corresponding aldehydes (1.0 eq.)…”
Section: Elemental Analysis (Chn)mentioning
confidence: 99%